DETERMINING PROJECTION AND SCALE FOR MAPS IN EARLY ATLASES OF CHINA HELD BY THE NATIONAL LIBRARY OF AUSTRALIA. - Jupp, David L. B. (Globe (0311-3930), 2018)
The National Library of Australia holds some maps and atlases from the 17th and 18th Century when cartography was between the period of manual construction of projections and the rise of mathematically defined projections. This paper shows how, despite their age, digital scanning and mathematical projections can often be used to geocode the maps and put them into a modern image processing format. This can create opportunities to study the comparative principal map scale, accuracy and historical contents of the collections. The digital maps can also be rescaled, reprojected and merged in mosaics using image processing. Where the atlases have gazetteers of points these can also be brought into the same framework and used to assess the underlying or potential accuracy of the map construction. The valuable nature of the collections introduces limitations and how these may be taken into account to allow the widest range of cases to be processed is discussed.